Influence Of The Compression Ratio And Ignition Timing On CB150R Engine Performance With 85% Bioethanol gasoline Blended Fuel - Yuli Mafendro Dedet Eka Saputra; Bambang Sudarmanta; Marthen Paloboran (IPTEK The Journal of Engineering, 2017)
Subtitution of the fuel type in the gasoline engine will change the setting The engine parameters as well as modify it to minimize engine performance degradation And increased exhaust emissions. Utilization of ethanol (85% vol.) - gasoline (15% vol.) The combination (E-85) for the gasoline engine requires some machine modifications and setting parameters due to differences in properties and characters between ethanol and gasoline. This study aims to test the effect of ignition timing and compression ratio on the performance of the engine and emission gas emissions. Ignition time varies between 16-24 Before Top Dead Center (BTDC) d. While the compression ratio variation consists of 11 (standart); 12, 12.5 and 13: 1. It was found that advancing the ignition time range 16o-24o BDTC with 13: 1 compression ratio can increase the performance of torque, bmep, and thermal efficiency respectively 7.94%, 5, 82% and 1.6% respectively, and a decrease of emissions of co and hc respectively 56.6% and 0.6% when compared with the performance of standard gasoline-fueled engines (E0).